Biologi Krustasea di Tracking Mangrove Kawasan Terusan Pulau Kemujan Kepulauan Karimunjawa - Kusumadewi, Irma; Pribadi, Rudhi; Widianingsih, Widianingsih (977-2407769)
The mangrove ecosystem of KarimunjawaNastional Park relatively good and natural used as ecotourism area. Karimunjawa National Park Authority provides facilities such as Mangrove Tracking. The existence of tracking mangrovepredicted can influence to the ecologycal condition of crustaceans, so it is necessary to study on crustaceans and its baseline data for monitoring environmental condition purposes due to the ecotourism area establishment. Sampling has be done on June 2012 – Maret 2013 at Mangrove Tracking Canal Zone Kemujan Island Karimunjawa Archipelago. Determination of sampling locations by using the method of purposive sampling method, then sampling used qualitative methods on 5m x 5m transect and quantitative on 1m x 1m transect. The results found crustaceans by 4 families and 6 species and 13 species of shrimp larvae. Infraordo Brachyura is the most dominant where found 3 families consist of 4 species, and then infraordo Anomura 1 families with 2 species and from infraordo Macrura found shrimp larvae. The most dominate type of crustacean from the result of this research is Clibanarius longitarsus. Crustacean abundance was highest at Station 5 (0.2 ind./25m2) and the lowest abundance at Station 7 (0.04 ind./25m2). Value diversity index (H’) and uniformity (e) are included in the low category and all research stations without domination.